Kebijakan Pendidikan Islam dalam Mengembangkan Karakter Peserta Didik: Abstract - Suryani, Eny; Subagyo, Ahmad; Hadi, Muhammad Sofian; Susanto, Ahmad (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Character development is important in building a nation's human resources. Islam not only emphasizes intellectual intelligence but also pays great attention to character and moral nobility as was the purpose of the sending of the Prophet Muhammad SWA. This article aims to describe and explain Islamic education policies in developing the character of students. Using a qualitative approach with a literature study method, this paper analyzes various Islamic education policies that have been published by the government and have an impact on the development of students' character through secondary data contained in several cases published in several research results and journals. The results of the analysis show that this policy shows a positive correlation in the formation and development of students' character where they not only have good intellectual abilities but also have positive character as a result of the application of Islamic religious values ??which are visible in several schools. The Islamic education policy in developing students' character is focused on several state high schools in South Tangerang City. The implications of this analysis show that the implementation of Islamic education policy plays a very significant role in the formation of students' character which is very useful in moving towards success and competition in the future in a global world which not only demands high intellectual abilities but also demands competitive character, hard work, not giving up easily and good behavior.